The Shadow of Totalitarianism : Action, Judgment, and Evil in Politics. - Burdman, Javier (State University of New York Press, 2022)
Examines the relationship of evil, action, and judgment in the work of Immanuel Kant, Hannah Arendt, and Jean-François Lyotard.
Description based upon print version of record.
Keywords: Arendt, Hannah, -- 1906-1975.; Lyotard, Jean-François, -- 1924-1998.; Kant, Immanuel, -- 1724-1804.; Arendt, Hannah, -- 1906-1975; Kant, Immanuel, -- 1724-1804; Lyotard, Jean-François, -- 1924-1998; Totalitarianism.; Good and evil.; Act (Philosophy); Judgment (Logic); Political science -- Philosophy.; Totalitarisme.; Action (Philosophie); Jugement (Logique); totalitarianism.; Good and evil; Political science -- Philosophy; Totalitarianism